Ground Truths Community-Engaged Research for Environmental Justice - Raphael, Chad; Matsuoka, Martha (University of California Press, 2024)
Ground Truths shows how community-engaged research contributes to environmental justice for Black, Indigenous, people of color, and low-income communities by centering local knowledge, building truth from the ground up, producing data that can influence decisions, and transforming researchers' relationships to communities for equity and mutual benefit. The book outlines the main steps in conducting community-engaged research, evaluates the major research methods used, and addresses institutional barriers to this kind of scholarship in academia. A critical synthesis of research in many fields, Ground Truths provides an original framework for aligning community-engaged research and environmental justice, and applies the framework in chapters on public health, urban planning, conservation, law and policy, community economic development, and food justice and sovereignty. "If you're looking for a primer on how to do community-engaged research in environmental justice, look no further." - MANUEL PASTOR, JR., Distinguished Professor of American Studies and Ethnicity, University of Southern California "Ground Truths offers a powerful journey into how the pursuit of knowledge can empower true change!" - KYLE WHYTE, George Willis Pack Professor of Environment and Sustainability, University of Michigan "Ground Truths demonstrates that mutually beneficial partnerships for research yield rich and sophisticated practices and outcomes." - TERESA CÓRDOVA, Professor of Urban Planning and Policy, University of Illinois at Chicago